Responding to domestic violence - Hoyle, C (1996)
This thesis aimed to understand the factors which shape the police and CPS response to domestic violence in the light of recent policy changes which recommended arrest in such cases. The decisions made by victims, police and prosecutors were charted in over one thousand three hundred reported cases of domestic violence in the Thames Valley during a seven month period in 1993. A random sample of 387 of these incidents were examined in detail. The study sought to understand the needs, desires and expectations of victims and how their choices impacted on the decisions made by police and prosecutors. Having evaluated feminist theories, the thesis argues that police and prosecutors do not randomly exercise their discretion nor can their response be explained by reference to cultural or individual prejudices. Rather, their decisions are best understood in terms of a set of informal 'working rules' developed by police and prosecutors for dealing with these complex and difficult cases. It is shown that whilst evidence of an offence was highly correlated with decisions regarding arrest and prosecution, evidence did not determine police action nor did its absence preclude such action. Rather, evidence facilitated police action where the working rules pointed towards an arrest. One of the strongest working rules related to the willingness of the victim to support a prosecution or not. The majority of victims did not want their partners or ex-partners to be prosecuted even when they had requested that the police arrest the perpetrators. Police and prosecutors believe the criminal justice system to be an extremely clumsy tool in dealing with domestic disputes. They therefore did not pursue independent evidence when victims withdrew their statements and they consequently discontinued these cases or did not initiate prosecution in the first place. Previous research has started from the premise that withdrawal of complaints by victims and the discontinuance of cases represents some kind of failure on the part of the agencies involved and that this would be remedied if the police arrested and prosecuted wherever possible. Implicit in this approach is the assumption that the criminal justice system as it presently operates is capable of responding effectively to the needs of victims of domestic violence. This thesis throws some doubt on the validity of these assumptions.